Analytical Geometrical Model of Open Cell Foams with Detailed Description of Strut‐Node Intersection1. Issue 7 (18th May 2017) - Ambrosetti, Matteo; Bracconi, Mauro; Groppi, Gianpiero; Tronconi, Enrico
Abstract: Open cell foams are regarded as potential enhanced catalyst carriers due to their high specific surface areas, low pressure drops, and good heat and mass transfer rates. However, it is difficult to evaluate their surface area. An analytical model is proposed, which is derived entirely from geometrical hypotheses and can be applied using different easily accessible input parameters. It can accurately estimate the specific surface and other features of foams for a wide range of porosities. The application of the new model to the reevaluation of published gas/solid mass transfer data is demonstrated. Abstract : The specific surface area of open cell foams is essential for the evaluation of their transport properties, in view of applications as catalyst support. An analytical model that is able to predict all geometrical features of foams has been developed, starting from two easily accessible parameters. Evaluation of published gas/solid mass transfer data with this model is demonstrated.